COLLECTIVE ACTION OF LOCAL CONSORTIUM FOR ENVIRONMENTAL GOVERNANCE: AN ANALYSIS FROM THE CAPITALS OF THE COMMUNITY (Biocenosis, 2013)
The establishment of local consortia within territories shared by different groups is a new experience for environmental governance in Central America. This initiative has promoted concrete political, economic and environmental actions that seek to improve peoples´ livelihoods and the sustainable use of natural resources. In this article, using systematization methodology and the Community Capital Framework, the main lessons learned from the process of creation of six local consortia by an international environmental organization working in a Central America region are described.
Keywords: Natural resources management; Social networks; Political capital; Natural capital; Social capital